Next‐Generation Sequencing of Circulating Tumor DNA Reveals Frequent Alterations in Advanced Hepatocellular Carcinoma. (1st March 2018) - Ikeda, Sadakatsu; Tsigelny, Igor F.; Skjevik, Åge A.; Kono, Yuko; Mendler, Michel; Kuo, Alexander; Sicklick, Jason K.; Heestand, Gregory; Banks, Kimberly C.; Talasaz, AmirAli; Lanman, Richard B.; Lippman, Scott; et al.
Abstract : Background: Because imaging has a high sensitivity to diagnose hepatocellular carcinoma (HCC) and tissue biopsies carry risks such as bleeding, the latter are often not performed in HCC. Blood‐derived circulating tumor DNA (ctDNA) analysis can identify somatic alterations, but its utility has not been characterized in HCC. Materials and Methods: We evaluated 14 patients with advanced HCC (digital ctDNA sequencing [68 genes]). Mutant relative to wild‐type allele fraction was calculated. Results: All patients (100%) had somatic alterations (median = 3 alterations/patient [range, 1–8]); median mutant allele fraction, 0.29% (range, 0.1%–37.77%). Mutations were identified in several genes: TP53 (57% of patients), CTNNB1 (29%), PTEN (7%), CDKN2A (7%), ARID1A (7%), and MET (7%); amplifications, in CDK6 (14%), EGFR (14%), MYC (14%), BRAF (7%), RAF1 (7%), FGFR1 (7%), CCNE1 (7%), PIK3CA (7%), and ERBB2/HER2 (7%). Eleven patients (79%) had ≥1 theoretically actionable alteration. No two patients had identical genomic portfolios, suggesting the need for customized treatment. A patient with a CDKN2A ‐inactivating and a CTNNB1 ‐activating mutation received matched treatment: palbociclib (CDK4/6 inhibitor) and celecoxib (COX‐2/Wnt inhibitor); des‐gamma‐carboxy prothrombin level decreased by 84% at 2 months (1, 410 to 242 ng/mL [normal: ≤7.4 ng/mL]; alpha fetoprotein [AFP] low at baseline). A patient with a PTEN ‐inactivating and a MET ‐activating mutation (an effect suggested by in silico molecular dynamic simulations) received sirolimus (mechanistic target of rapamycin inhibitor) and cabozantinib (MET inhibitor); AFP declined by 63% (8, 320 to 3, 045 ng/mL [normal: 0–15 ng/mL]). Conclusion: ctDNA derived from noninvasive blood tests can provide exploitable genomic profiles in patients with HCC. Implications for Practice: This study reports that blood‐derived circulating tumor DNA can provide therapeutically exploitable genomic profiles in hepatocellular cancer, a malignancy that is known to be difficult to biopsy. Abstract : This article reports unique aspects of the management of hepatocellular carcinoma. The study aimed to determine if next‐generation sequencing of blood‐derived circulating tumor DNA from patients with hepatocellular carcinoma could identify actionable somatic molecular alterations. Illustrative examples of treated patients and of in silico molecular dynamic simulation to reveal genomic variant function are included.